Question
upstudy study bank question image url

Si \( a=-3, b=2 \) et \( c=-1 \) CALCULE la valeur numério \( a^{2}-c=-b^{2}+1 \)

Ask by Turnbull Robbins. in Belgium
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

Avec les valeurs \( a=-3 \), \( b=2 \) et \( c=-1 \), l'équation \( a^{2}-c=-b^{2}+1 \) n'est pas vérifiée.

Solution

Solve the equation by following steps: - step0: Solve for \(a\): \(a^{2}-c=-b^{2}+1\) - step1: Move the expression to the right side: \(a^{2}=-b^{2}+1+c\) - step2: Simplify the expression: \(a=\pm \sqrt{-b^{2}+1+c}\) - step3: Separate into possible cases: \(\begin{align}&a=\sqrt{-b^{2}+1+c}\\&a=-\sqrt{-b^{2}+1+c}\end{align}\) Pour résoudre l'équation \( a^{2}-c=-b^{2}+1 \) avec les valeurs données \( a=-3 \), \( b=2 \) et \( c=-1 \), nous allons d'abord substituer ces valeurs dans l'équation. 1. **Substitution des valeurs** : \[ (-3)^{2} - (-1) = - (2)^{2} + 1 \] 2. **Calcul des carrés** : \[ 9 + 1 = -4 + 1 \] 3. **Simplification** : \[ 10 = -3 \] Il semble que l'équation ne soit pas vérifiée avec les valeurs données. Pour trouver la valeur de \( a \) en fonction de \( b \) et \( c \), nous avons déjà obtenu : \[ a = \sqrt{-b^{2}+1+c} \quad \text{ou} \quad a = -\sqrt{-b^{2}+1+c} \] Calculons maintenant \( -b^{2}+1+c \) avec \( b=2 \) et \( c=-1 \) : \[ -b^{2}+1+c = -2^{2}+1+(-1) = -4 + 1 - 1 = -4 \] Puisque la racine carrée d'un nombre négatif n'est pas définie dans les réels, cela signifie qu'il n'y a pas de solution réelle pour \( a \) dans cette équation avec les valeurs données. En conclusion, l'équation \( a^{2}-c=-b^{2}+1 \) n'est pas vérifiée pour \( a=-3 \), \( b=2 \) et \( c=-1 \).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

The Deep Dive

Pour résoudre l'équation \( a^{2}-c=-b^{2}+1 \) avec les valeurs données \( a=-3, b=2 \) et \( c=-1 \), commençons par substituer les valeurs : 1. Calculons \( a^{2} \) : \[ a^{2} = (-3)^{2} = 9 \] 2. Maintenant, remplaçons \( c \) par -1 dans l'équation : \[ a^{2} - (-1) = 9 + 1 = 10 \] 3. Calculons \( -b^{2} + 1 \) : \[ -b^{2} = -2^{2} = -4 \] Donc : \[ -b^{2} + 1 = -4 + 1 = -3 \] Ensuite, remplaçons tout cela dans l'équation pour obtenir : \[ 10 = -3 \] Il semble qu'il n'y ait pas d'égalité, donc l'équation est fausse avec les valeurs de \( a \), \( b \) et \( c \) données.

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy